SOCIAL CAPITAL AND STUDENT ACHIEVEMENT: A SYSTEMATIC LITERATURE REVIEW OF FAMILY, COMMUNITY, AND INSTITUTIONAL INFLUENCES - Hikmat (GoAcademica CRP, 2025)
This study conducts a systematic literature review to explore the relationship between social capital and student achievement by examining family, community, and institutional influences. Social capital, as a multidimensional construct, plays a critical role in shaping educational outcomes through networks, trust, and reciprocal norms. The review synthesizes findings from peer–reviewed journal articles retrieved from major academic databases, with a focus on studies published within the last two decades. Family involvement, including parental support and socioeconomic resources, consistently emerges as a fundamental determinant of academic success. Community factors such as peer networks, neighborhood safety, and cultural expectations also demonstrate significant but varied impacts on student learning trajectories. Institutional influences, particularly school resources, teacher–student interactions, and extracurricular participation, further enhance the development of educational capital. The review highlights how these three domains interact dynamically, suggesting that student achievement cannot be explained by isolated factors. Despite the abundance of studies, notable gaps remain in integrating these influences into a comprehensive theoretical framework. The findings emphasize the importance of adopting holistic approaches in policy and practice to leverage social capital for educational improvement. This study contributes to the discourse by providing a consolidated understanding of how family, community, and institutional dimensions collectively shape student achievement.